Experimental and numerical study on an innovative protective measure for high strength concrete using the bilayer method. (January 2023) - Shan, Zhiwei; Wu, Zhuoya; Lo, S.H.; Su, R.K.L.
Abstract: Fire-induced spalling is an ongoing primary concern in the application of high-strength concrete in building structures. A reliable and practical protective method is thus highly desirable and critical for the prevention of fire-induced spalling. Therefore, an innovative bilayer method, in which high strength concrete is surrounded by a layer of normal strength concrete of sufficient thickness, is proposed. A total of 20 columns are cast to investigate the feasibility of the bilayer design, of which 15 are put to fire testing and the other five to ambient compression testing. The effects of protective layer thickness, duration of exposure to fire, sealed condition and reinforcement confinement are investigated. Experimental results indicate that the performance of bilayer columns is similar to that of high strength concrete columns with regard to strength and deformation. Fire-induced spalling occurs within the first 30 min of heating at an interface temperature of around 150 °C. Lastly, a minimum effective thickness of 100 mm is recommended to prevent spalling.